FTO Gene Polymorphisms at the Crossroads of Metabolic Pathways of Obesity and Epigenetic Influences - Popović, Ana-Marija; Huđek Turković, Ana; Žuna, Kristina; Bačun-Družina, Višnja; Rubelj, Ivica; Matovinović, Martina (Food technology and biotechnology, 2023)
In this review, we summarize the current state of knowledge on the fat mass and obesity-associated (FTO) gene and its role in obesity. The FTO-encoded protein is involved in multiple molecular pathways contributing to obesity as well as other metabolic complexities. This review emphasizes the epigenetic influence on the FTO gene as a new approach in the treatment and management of obesity. Several known substances have a positive effect on reducing FTO expression. Depending on which variant of the single nucleotide polymorphism (SNP) is present, the profile and level of gene expression changes. Implementation of environmental change measures could lead to reduced phenotypic manifestation of FTO expression. Treating obesity through FTO gene regulation will have to include various complex signal pathways in which FTO takes part. Identification of FTO gene polymorphisms may be useful for the development of individual obesity management strategies, including the recommendation of taking certain foods and supplements.